Index Card Match as an Interactive Strategy to Improve Elementary School Students' Science Learning Activeness - Nur Hikma Maulia; Erma Suryani Sahabuddin; Nur Abidah Idrus (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aimed to explore whether the Index Card Match learning model could boost student engagement in science lessons for fourth-grade pupils at UPT SDN 83 Mangindara. We took a descriptive qualitative approach, focusing on how the model was applied and its impact on student activities. The research happened at UPT SDN 83 Mangindara in Takalar Regency during the 2024/2025 school year, involving 22 fourth-grade students 7 girls and 15 boys. Data came from observations, tests, and documentation, analyzed through qualitative descriptive methods. The findings showed that using the Index Card Match model in science classes did enhance student learning activities at UPT SDN 83 Mangindara. In Cycle I, activities were low in the first meeting (categorized as